Estudo da eletrodeposição de Ni e Ni+SiC para liga de Al AA 6061 - Folquenin, Geison André (2010)
Aluminum alloys are largely used, because the properties they provide, such as reducing weight while maintaining strength and durability in mechanical systems. The corrosion of Al occurs in the form of pits (points alveolar surface) and the sequence can occur inter granulated oxidation of a metal matrix, which compromises their resistance. Surface treatments are used to improve corrosion resistance and increased hardness of the metal surface. The electrodeposition of nickel is a technique used to provide changes of surface properties of metal. The addition of nanoparticles of SiC (silicon carbide), the deposition process can provide desirable characteristics to the surface with the formation of nanocomposites (metal-ceramic). Few studies have been conducted on the electrodeposited composite coatings on Al alloys and improvement in properties such as hardness and corrosion resistance. The aim of this paper is to study the electrochemical plating of nickel on the surface of an aluminum alloy 6061, in the absence and presence of SiC. This study used techniques, such as open circuit potential, chronoamperometry, nucleation-growth-overlap curves, anodic potentiodynamic polarization, electrochemical impedance spectroscopy (EIS), hardness measurements and optical microscopy and scanning electron microscopy (SEM). Initial results show that the nucleation in nickel on the surface of the alloy occurs instantaneously, the polarization curves show that the behavior of aluminum alloy with nickel deposit is similar to the nickel + silicon carbide, suggesting that this layer causes the protection of the base metal. SEM results show that the presence of SiC is a change in the deposition of nickel on the surface of aluminum alloy. In many results of EIS performed in the potential for corrosion of aluminum alloy deposited nickel, there were arches characteristic impedance of passive materials. Micro hardness analyzed the base metal containing a layer of Ni + SiC had a budget of approximately 176% compared to only aluminum, 194 HV.